UNCOVERING THE MARRIAGE LIFE OF MODERN MADURESE WOMEN: THE SEXUAL CONTRACTS THEORY - Miftahur Roifah; Zakiyatul Mufidah (Universitas 17 Agustus 1945 Surabaya, 2022)
The life of Madurese women is interesting to study as they live in a strongly patriarchal society as well as cultural traditions. In terms of marriage, Madurese women are confronted with unfavorable traditional practices such as early marriage and arranged marriage. Low educational level and financial dependence are two major factors that prevent them from escaping these practices and leave them in unhappy marriages. Many of them experience domination and subordination in all aspects of their life. However, such conditions are commonly experienced by former Madurese women whose life was restricted to beliefs and traditions that undermined women. Nowadays, modern era has significantly shaped the way people perceive things and behave. Subsequently, modern Madurese women are rejecting the existing marriage traditions by marrying the men of their choosing. They also have better educational backgrounds that contribute to the different perspectives of life and are financially independent. Employing a phenomenological framework, the purpose of this study is to investigate the marriage life of Modern Madurese women by looking at the husband-wife relationship based on the sexual contracts theory. Unstructured interviews were used to generate the data for the analysis. The results of the study demonstrate that there is a husband-wife relationship shifting in the marriage life of modern Madurese women. The husband-wife relationship is more to the partnership rather than dominant-subordinated.